E-cigarette, or Vaping, Product Use-Associated Lung Injury—Lessons Learned: A Case Series. Issue 8 (June 2020) - Helm, Cole; Labovsky, Kristen; Thakrar, Pooja D.; Diaz, Christina D.
Abstract : E-cigarette, or vaping, product use has been declared an epidemic, and a new disease has emerged from their use. We describe 4 patients with significant acute lung injury related to e-cigarette use who underwent bronchoscopy and bronchoalveolar lavage. All cases posed anesthetic challenges, including increased airway reactivity, hypoxia, increasing oxygen requirements, and, in 2 severe cases, the need for continued postprocedural mechanical ventilatory support. It is imperative that all members of the treating team are aware of the disproportionate risk of respiratory complications to anticipate the possible need for increased postprocedural respiratory support. Abstract : Supplemental Digital Content is available in the text.